Comparison of Biogenic Amorphous Silicas Found in Common Horsetail and Oat Husk With Synthetic Amorphous Silicas - Lindner, Gottlieb Georg; Drexel, Claus-Peter; Sälzer, Katrin; Schuster, Tobias B.; Krueger, Nils (Frontiers in Public Health, 2022)
The present paper summarizes literature on the presence and the structure of biogenic amorphous silica (BAS) in nature. Based on this review it could be shown that BAS is ubiquitous in nature and exhibits a structure which cannot be differentiated to the structure of synthetic amorphous silica (SAS). The structural similarity of BAS and SAS are further supported by own investigations – in particular specific surface area (BET) and electron microscope techniques - on oat husk and common horsetail. Many food products containing BAS are considered as being beneficial to health. In context with SAS in specific applications (e.g. food, feed, cosmetics) this is of special interest for the discussion of the safety of these applications.